Consumo del jarabe valganciclovir elaborado en el Servicio de Pediatría Especializada del Hospital Edgardo Rebagliati Martins – EsSalud, 2018 – 2019 - Paredes Puerta, Alexandra Fiorela (2020)
The objective of this work was to quantify the consumption of the syrup valganciclovir magisterial preparation for the specialized pediatric service during the years 2018 and 2019. The production records of the Pharmacotechnical area of sterile preparations of the Edgardo Rebagliati Martins Hospital were used. Monthly consumption, annual average and consumption trend over time were quantified. The consumption of valganciclovir syrup increased in 2019, with September being the month with the highest formulation, representing 13%, demonstrating a positive consumption trend during the rotation time in the service. It is concluded that the consumption of this magisterial formulation is increasing due to the analysis of indicators presented in the Pharmacotechnical service of the Edgardo Rebagliati Martins Hospital